(untitled) (Biocenosis, 2014)
This research project aimed to identify the perception of coastal communities around Cabo Blanco about the use and management of coastal marine resources in the area. A consultation workshop carried out in Montezuma, Puntarenas,the communities indicated the importance of the Natural Absolute Reserve Cabo Blanco in regards to the protection of zones of waters recharge and beaches for tourism and turtles nesting. Some of the problems identified by the communities were the scarce drinking water supply, a lack of a permanent system of garbage recollection, and illegal fishing within the Reserve. The communities suggest an integrated management of the coastal marine resources starting from the watershed and higher government participation. Because of the low level of public participation in the process of integrated coastal management in tropical regions the importance of these experiences in the promotion of participative processes to integrally understand the dynamic of the coastal zone in the country is emphasized.